184 Right data, right care. Issue 6 (27th May 2022) - Biggin, Fran; Knight, Jo; Emsley, Hedley
Abstract : There is considerable current interest in neurology 'intelligence'. For example, NHS RightCare uses nation- ally collected data to identify and address variations in care, and the clinically led NHS improvement programme Getting It Right First Time seeks to improve quality of care by reducing variation. Despite this, current neurology 'intelligence' strategies lack data on clinic activity because outpatient coding is not routinely done. In order to determine what insights can be gained from routine data, we have analysed data collected at a neurology outpatient clinic (5902 appointments for 3100 patients) offered by one neurologist (HE) over three years. We found clear patterns in variables such as age distributions, interval from referral to appointment by conditions, and geographical source of referral. The data can be presented in a format useful for clini- cians and service managers, allowing identification of opportunities for change such as optimal utilisation of alternative pathways for management of primary headache disorders. In order to be most useful, this type of analysis should be available across all Neurology outpatient services. However various barriers including workforce, non-standardised approaches to outpatient coding, and variation in IT systems hamper implementation. Our ongoing collaborative project seeks to meet these challenges. f.biggin@lancaster.ac.uk